Hubungan Social Comparison dengan Gejala Depresi pada Mahasiswa Pengguna Instagram - Salsabila Auliannisa; Muhammad Ilmi Hatta (Jurnal Riset Psikologi, 2021)
Abstract. College student need to evaluate themselves, this can be through social comparison. Instagram can be a media for social comparison, because there are photo and video posts from other users. Instagram is an image-based platform that allows users to more easily express themselves, so the content is usually aesthetic and optimized. Thus, the social comparisons made on Instagram are different from the comparisons made in real life. On social media such as Instagram, published information is always the best view of oneself rather than the bad things of a person. If social comparison is done negatively, it can lead individuals to feel negative emotions that are in symptoms of depression. Similarly, individuals with depressive symptoms tend to compare themselves when using Instagram, seeing that other people's lives seem better can lead to negative self-evaluation. This study aims to determine the degree of the relationship between social comparisons and depressive symptom in college students using Instagram is. The research method used is correlational method with 112 college students using Instagram as respondents. The measuring instruments used are the Social Comparison Rating Scale and the Beck Depression Inventory–II. The analysis technique used Rank Spearman correlation technique. The results showed that there was a moderate relationship between social comparisons and depressive symptoms with a correlation value of -0.435 and p-value (Sig.) = 0.000. The direction of the relationship between variables is negative, meaning that the lower the social comparison score, the higher the score for depression symptoms in college students who use Instagram. Abstrak. Mahasiswa memiliki kebutuhan untuk mengevaluasi dirinya, hal ini dapat dipenuhi melalui social comparison. Instagram dapat menjadi sarana social comparison, karena terdapat postingan foto dan video dari penggunalain. Instagram adalah platform berbasis gambar yang membuat penggunanya dapat lebih mudah mengekspresikan diri, sehingga konten yang diunggah biasanya bersifat estetika dan dioptimalkan. Sehingga, social comparison yang dilakukan di Instagram berbeda dengan perbandingan yang dilakukan di kehidupan nyata. Pada media sosial seperti Instagram informasi yang dipublikasikan selalu tampilan terbaik diri daripada hal yang buruk dari diri seseorang. Jika social comparison dilakukan secara negatif, dapat mengarahkan individu merasa emosi negatif yang ada dalam gejala depresi. Begitu pula, individu dengan gejala depresi cenderung membandingkan diri mereka sendiri saat menggunakan Instagram, melihat bahwa kehidupan orang lain tampak lebih baik dapat membuat menilai diri sendiri secara negatif. Tujuan penelitian ini adalah untuk mengetahui seberapa erat hubungan antara social comparison dengan gejala depresi pada mahasiswa pengguna Instagram. Metode penelitian yang digunakan adalah korelasional dengan responden 112 orang mahasiswa pengguna Instagram. Alat ukur yang digunakan adalah Social Comparison Rating Scale dan Beck Depression Inventory – II. Teknik analisis penelitian ini menggunakan Rank Spearman. Hasil penelitian menunjukan terdapat hubungan sedang/moderate antara social comparison dengan gejala depresi dengan nilai korelasi sebesar -0,435 dan dan p-value (Sig.) = 0,000. Arah hubungan antar variabel negatif artinya semakin rendah skor social comparison maka semakin tinggi skor gejala depresi pada mahasiswa pengguna Instagram.